Equivalent crossed products of monoidal Hom-Hopf algebras - Wang, Zhongwei (Array, 2019)
In this paper, we give a Maschke-type theorem for a Hom-crossed product on a finite dimensional monoidal Hom-Hopf algebra, and investigate a sufficient and necessary condition for two Hom-crossed products to be equivalent. Furthermore, we construct an equivalent Hom-crossed system based on a same Hom-crossed product by using lazy Hom-2-cocyle.